ANALISIS DAMPAK INTERNAL YANG MEMPENGARUHI AUDIT DELAY - I Dewa Made Endiana; I Kadek Apriada (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus, 2020)
Audit delay is the time span required by the auditor to complete the audit task on the financial statements which can be calculated from the closing date of the company's books, 31 December to the date of issuance of the audit report. This study aims to determine the effect of profitability, solvency, activity and company age on audit delay. The research sample was 39 property and real estate companies. The results showed that profitability and activity had a negative effect on audit delay, solvency had no effect on audit delay, while company age had a positive effect on audit delay